A seamless repository for pervasive teamwork. (2016) - Wu, Yilang; Wang, Junbo; Hsu, Hui-Huang; Cheng, Zixue
Mobile cloud-based collaborative workflow has pervasively empowered teamwork. However, it still suffers from collaborative workflow barriers, such as workflow complexity, poor communication, and teamwork disruption. To ease collaborative workflow barriers, we propose and develop a seamless repository by integrating multiple support systems into a three-layered framework. Under the premises of availability, connectivity, and transparency, the three-layered seamless repository strengthens the collaborative workflow in pervasive teamwork. It supports various critical collaborative workflow activities such as issue tracking, revision control, content management, system visualisation, onsite participation tracking, and team communication. After a test period of one year, active teamwork involvement has been observed, which implies that the barriers are relieved. Furthermore, several hidden patterns of teamwork are discovered through the seamless repository, which are useful to improve future support for pervasive teamwork.